Occupational risk factors for pancreatic cancer among female textile workers in Shanghai, China. Issue 12 (17th July 2006) - Li, W; Ray, R M; Gao, D L; Fitzgibbons, E D; Seixas, N S; Camp, J E; Wernli, K J; Astrakianakis, G; Feng, Z; Thomas, D B; Checkoway, H
Abstract : Objectives To investigate whether occupational exposures to dusts and chemicals in the Shanghai textile industry are associated with risk of pancreatic cancer. Methods A case cohort study nested in a cohort of 267 400 female textile workers in Shanghai, China was conducted among 180 incident pancreatic cancer cases and an age stratified randomly selected comparison subcohort (n = 3188). A complete occupational history of work in the textile industry was obtained for each woman, and was linked to a job exposure matrix developed for the textile industry to estimate exposures to specific dusts and chemicals. Cumulative exposures to cotton dust and endotoxin were reconstructed from historical and contemporaneous measurements. Results After adjusting for smoking status, a trend of decreasing risk of pancreatic cancer was observed for increasing cumulative exposures to cotton dust and endotoxin with a lag of 20 years. The hazard ratios for women cumulatively exposed to >143.4 mg/m 3 × years of cotton dust and >3530.6 EU/m 3 × years of endotoxin were 0.6 (95% CI 0.3 to 0.9) and 0.5 (95% CI 0.3 to 0.9), respectively, compared to unexposed women. There was little evidence that exposures to other textile dusts and chemicals were associated with risk of pancreatic cancer. Conclusions Occupational exposure to cotton dust and endotoxin in the textile industry may have reduced risks of pancreatic cancer in this cohort. These associations should be replicated by others before making a firm conclusion of their possible effects on pancreatic cancer.